Role of Cytosolic Serine Hydroxymethyl Transferase 1 (SHMT1) in Phosphate-Induced Vascular Smooth Muscle Cell Calcification - Beate Boehme; Nadeshda Schelski; Manousos Makridakis; Laura Henze; Antonia Vlahou; Florian Lang; Burkert Pieske; Ioana Alesutan; Jakob Voelkl (Karger Publishers, 2018)
Background/Aims: Hyperphosphatemia promotes medial vascular calcification, at least partly, by induction of osteo-/chondrogenic transdifferentiation of vascular smooth muscle cells (VSMCs). The complex signaling pathways regulating this process are still incompletely understood. The present study investigated the role of cytosolic serine hydroxymethyl transferase 1 (SHMT1) in phosphate-induced vascular calcification. Methods: Endogenous expression of SHMT1 was suppressed by silencing in primary human aortic smooth muscle cells (HAoSMCs) followed by treatment without and with phosphate or antioxidants. Results: In HAoSMCs, SHMT1 mRNA expression was up-regulated by phosphate. Silencing of SHMT1 alone was sufficient to induce osteo-/chondrogenic transdifferentiation of HAoSMCs, as shown by increased tissue-nonspecific alkaline phosphatase (ALPL) activity and osteogenic markers MSX2, CBFA1 and ALPL mRNA expression. Furthermore, phosphate-induced ALPL mRNA expression and activity as well as calcification were augmented in SHMT1 silenced HAoSMCs as compared to negative control siRNA transfected HAoSMCs. Silencing of SHMT1 decreased total antioxidant capacity and up-regulated NADH/NADPH oxidase system components NOX4 and CYBA mRNA expression in HAoSMCs, effects paralleled by increased mRNA expression of matrix metalloproteinase MMP2 as well as BAX/BCL2 ratio. More importantly, additional treatment with antioxidants TEMPOL or TIRON blunted the increased osteogenic markers mRNA expression in SHMT1 silenced HAoSMCs. Conclusion: Silencing of SHMT1 promotes osteo-/chondrogenic signaling in VSMCs, at least in part, by inducing cellular oxidative stress. It thus aggravates phosphate-induced calcification of VSMCs. The present findings support a regulatory role of SHMT1 in vascular calcification during conditions of hyperphosphatemia such as chronic kidney disease.